Quality Perception of Spotify's Purchase Intentions in Indonesia - Zee Zee Aprilia (Jurnal Indonesia Sosial Teknologi, 2024)
This study investigates the correlation between perceived quality and purchase intention within the domain of music streaming services, focusing on Spotify. Employing a quantitative-descriptive approach, the research utilizes surveys for data collection and employs simple linear analysis to scrutinize the relationship between independent and dependent variables. The results underscore a statistically significant positive influence of perceived quality on purchase intention.